UPAYA PENANGULANGAN KEJAHATAN TERORISME YANG BERKARAKTERISTIK HAK ASASI MANUSIA DI INDONESIA - Ridwan Ridwan (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2010)
Indonesia is the country founded on law and not only power. Hence, the tackling of terrorism as a criminal offense must also be founded on law, respect and protection of human rights of the suspect, defendant, and convict. Human rights are guaranteed by the positive law in Indonesia. The party alleged as the terrorist can be arrested for two years without a trial, is not in accordance with the law founded on Pancasila which requires a guarantee for a just and civilized humanity to create justice for all Indonesian people based on the supreme of law. Any violation of law by anyone including the law enforcer cannot be justified. Consequently, a criminal policy is necessary by using penal and non-penal tools so that the law can be enforced effectively without endangering the value of legal basis in the forms of legal certainty, justice, and expediency. The law enforcement must also be accompanied by faith to avoid violation of law. Thus, the tackling of crime related to terrorism really characterizes human rights enforcement founded on the value of legal basis.